Glycemic index: effect of food storage under low temperature - Carreira,Marina Cassab (2004)
This study was carried out to evaluate the influence of food storage under low temperature (-20ºC) and the resistant starch formation, both on the glycemic index (GI). The GI of only cooked and cooked and stored foods under -20ºC for 30 days was evaluated in short-term tests with humans. Significant increase on the RS content was evidenced for all the stored foods. The food storage resulted in a significant decrease on the GI of beans and chick-peas; the GI of pasta remained the same and the GI of corn meal increased. Thus, the RS formation showed reduced influence on the glycemic index. The storage of starchy foods under low temperature can collaborate to the RS intake but its effect on the GI will depend on the characteristics of the carbohydrates of each food.